Governance Ethics in Healthcare Organizations - Magill, Gerard (Routledge Studies in Health and Social Welfare, 2020)
Drawing on the findings of a series of empirical studies undertaken with boards of directors and CEOs in the United States, this groundbreaking book develops a new paradigm to provide a structured analysis of ethical healthcare governance. Governance Ethics in Healthcare Organizations begins by presenting a clear framework for ethical analysis, designed around basic features of ethics - who we are, how we function, and what we do - before discussing the paradigm in relation to clinical, organizational and professional ethics. It goes on to apply this framework in areas that are pivotal for effective governance in healthcare: oversight structures for trustees and executives, community benefit, community health, patient care, patient safety and conflicted collaborative arrangements. This book is an important read for all those interested in healthcare management, corporate governance and healthcare ethics, including academics, students and practitioners.